Improvement of Solar Energy System Under Partial Shading Conditions in Koneru Lakshmaiah Education Foundation - Bhargavi, B; Linga Reddy, P (International Journal of Engineering and Technology, 2018)
This paper consists of grid connected Solar photovoltaic (SPV) system. An output of SPV depends on the irradiation and temperature. Sometimes PV module is shaded due to nearby buildings, passing clouds etc. Power extracted from such partially shaded PV array is reduced. . The PV system at KLEF deemed to be university is considered. Total Harmonic Distortion (THD) and the output powers  are  computed using Matlab/Simulink using LC filter .These are compared with the actual values measured from the existing system . It is found that percentage of THD is reduced.